Increased mortality among people with anxiety disorders: total population study - Meier, Sandra M.; Mattheisen, Manuel; Mors, Ole; Mortensen, Preben B.; Laursen, Thomas M.; Penninx, Brenda W. (British journal of psychiatry, 2016)
Anxiety disorders and depression are the most common mental disorders worldwide and have a striking impact on global disease burden. Although depression has consistently been found to increase mortality; the role of anxiety disorders in predicting mortality risk is unclear. To assess mortality risk in people with anxiety disorders. We used nationwide Danish register data to conduct a prospective cohort study with over 30 million person-years of follow-up. In total, 1066 (2.1%) people with anxiety disorders died during an average follow-up of 9.7 years. The risk of death by natural and unnatural causes was significantly higher among individuals with anxiety disorders (natural mortality rate ratio (MRR) = 1.39, 95% CI 1.28-1.51; unnatural MRR = 2.46, 95% CI 2.20-2.73) compared with the general population. Of those who died from unnatural causes, 16.5% had comorbid diagnoses of depression (MRR = 11.72, 95% CI 10.11-13.51). Anxiety disorders significantly increased mortality risk. Comorbidity of anxiety disorders and depression played an important part in the increased mortality.